The effect of captopril on simple-hypothermic preservation of kidneys [Bobreklerin basit-hipotermik korunmasinda kaptopril'in etkisi] - (:unkn) unknown (AVES, 1998)
In previous studies it has been shown that when CPT is used systematically, it is able to bind free oxygen radicals and increase the endothelin concentration, thus plays a preventive role in ischemic changes in kidneys, liver and small intestine. The aim of this study is to clarify the role of CPT when added to EuroCollins solution in the preservation of kidneys. The study has been performed on 3 groups, each containing 6 rats. Ringer lactate, EuroCollins and EuroCollins enriched with CPT (5 mg/ml) were perfused to group 1,2 and 3 respectively. Then their left kidneys were removed and preserved in the same solutions under 4°C temperature. Biopsies were taken with time intervals and studied under electron microscope. While great damage was confirmed in the 3(rd) hour in group 1, the same damage was seen in the 6(th) hour in the 2(nd) group. Biopsies which are taken at 6(th) hour in group 3 showed less damage when compared with group 2. The morphologic changes seen under electron microscope made us to believe that the addition of CPT to preservation solutions helps in delaying tissue damage.
Keywords: Captopril; Kidney